The Challenges of e-Procurement Implementation in Infrastructure Projects - Rizki, Alisia Ardita (FIA UB, 2018)
This paper aims to explore the challenges of e-procurement implementation and how to overcome these challenges in infrastructure project of Ministry of Public Work and Housing. This study used secondary data analysis such as blue print, activity report, performance report and financial report. The data were collected on January 2018. The findings show that there are two key challenges of e-procurement implementation. Challenges in system specification are not only related to software integration and data management, but also legal and administration procedures and IT infrastructure. Challenges in implementation management are related to roll-out strategy and IT skills. However, there is no issue in IT outsourcing. Findings also show that there are impacts of e-procurement implementation on total cost of acquisition, organizational characteristics, and governance structure. Challenges can be overcome by establishing integrated e-procurement system and centralized database.